2015
DOI: 10.1371/journal.pone.0131868
|View full text |Cite
|
Sign up to set email alerts
|

Dual Roles of the Lysine-Rich Matrix Protein (KRMP)-3 in Shell Formation of Pearl Oyster, Pinctada fucata

Abstract: Matrix proteins play important roles in shell formation. Our group firstly isolated three cDNAs encoding lysine-rich matrix protein from Pinctada fucata in 2006. However, the functions of KRMPs are not fully understood. In addition, KRMPs contain two functional domains, the basic domain and the Gly/Tyr domain respectively. Based on the modular organization, the roles of their two domains were poorly characterized. Furthermore, KRMPs were then reported in other two species, P. maxima and P. margaritifera, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 44 publications
1
32
0
Order By: Relevance
“…The extracted matrix proteins can be classified as soluble proteins and insoluble proteins after the decalcification treatment by EDTA. Even though the insoluble matrix proteins were generally thought to be structural proteins that are responsible for the formation of the organic framework, some of these proteins have been reported to participate in the regulation of shell biomineralization (30,43). Here, we observed that the matrix protein Shematrin-2 is present in the EISM of shell nacreous and prismatic layers and in the extrapallial fluid where shell biomineralization occurs (Fig.…”
Section: Transcriptional Regulation Of Matrix Protein Shematrin-2mentioning
confidence: 65%
“…The extracted matrix proteins can be classified as soluble proteins and insoluble proteins after the decalcification treatment by EDTA. Even though the insoluble matrix proteins were generally thought to be structural proteins that are responsible for the formation of the organic framework, some of these proteins have been reported to participate in the regulation of shell biomineralization (30,43). Here, we observed that the matrix protein Shematrin-2 is present in the EISM of shell nacreous and prismatic layers and in the extrapallial fluid where shell biomineralization occurs (Fig.…”
Section: Transcriptional Regulation Of Matrix Protein Shematrin-2mentioning
confidence: 65%
“…The organic materials include matrix proteins, polysaccharides, lipids and other small molecules. And the matrix proteins are proved to be involved in calcium carbonate nucleation, polymorphs selection, crystal orientation, and have been extensively studied (Liang et al, 2015; Miyamoto et al, 1996; Ponce and Evans, 2011; Takeuchi et al, 2008). It has been demonstrated that many matrix protein genes were upregulated after shell damage stimulation (Kong et al, 2009; Lin et al, 2014) and some SMPs have been proved to promote nucleation of calcium carbonate, such as PfY2 (Yan et al, 2017), Alv (Kong et al, 2018) and Prismalin-14 (Suzuki et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…In vitro crystal growth experiments [29] were performed to test the effects of rWLP on the morphology of calcite and aragonite crystals. The rWLP was incubated in a freshly prepared saturated solution of calcium carbonate [30] on a siliconized cover glass with or without magnesium chloride.…”
Section: Functional Analysis Of Rwlpmentioning
confidence: 99%
“…The inhibition of the rWLP on calcium carbonate precipitation was tested using the methods provided by Liang et al [29] with minor modifications. Briefly, a 10 mM calcium chloride solution containing rWLP at various concentrations (10, 30, and 50 μg/mL) was dropped into a 96-well plate, and the plate was placed in a closed desiccator.…”
Section: Functional Analysis Of Rwlpmentioning
confidence: 99%
See 1 more Smart Citation